The complete mitochondrial genome of Yao silkworm (Bombyx mori). Issue 2 (3rd July 2019) - Zhang, Gui-Zheng; Huang, Wen-Gong; Zhang, Yu-Li; Liu, Yan-Wei; Huang, Hua-Xu; Liu, Yan-Qun; Bi, Li-Hui; Lu, Cheng
Abstract: Here, we describe the first complete mitochondrial genome of Yao silkworm, a unique silkworm resource native at Guangxi, China. This circular molecule is 15, 656 bp long and contains the typical set of 37 genes (13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes) and one non-coding A + T-rich region of 494 bp long. The genome organization and gene arrangement are identical to those observed in all available Bombyx mori strains. The phylogenetic tree inferred from Bayesian inference provides a molecular evidence that Yao silkworm belongs to the domestic silkworm ( B. mori ), rather than a novel silkworm species.